The Effect of Self-Citation on Scholarly Recognition and Visibility - Aljarah, Ibrahim (Jordan Medical Journal, 2024)
Self-citation, an important aspect of academic work [1], requires careful oversight to protect the integrity and perception of scholarly contributions. Although self-referencing is often necessary for expanding upon past research, an excessive amount can negatively affect a researcher’s reputation and rankings in academic indices. Indices/Lists like the Highly Cited Researcher (HCR) [2] index by Clarivate Analytics often adjust or exclude metrics associated with high self-citation rates to provide a more accurate representation of a researcher’s impact, thereby enhancing visibility and credibility. According to the authors of [3] [4], self-citation rates typically range from 7.38% in Economics & Business to 15.6% in Mathematics. The same authors in [3] recommend keeping self-citations below 10%, which aligns with the general agreement among academic institutions and researchers. Maintaining this limit helps in qualifying for prestigious rankings and awards, promoting fair competition in academia. There are several methods to verify the self-citation ratio, with two of the most popular ones being the use of the Scopus platform [5] and the Web of Science (WOS) portal by Clarivate [6]. Scopus and WOS do not directly display the self-citation rate, but they do offer both the total citation count and the count excluding self-citations. Additionally, these portals can generate a citation report for authors, providing details on the number of citations, h-index, citing articles (with an option to exclude self-citations), and a year-by-year breakdown of citation counts. To find the self-citation rate Scopus and WOS, subtract the number of citations excluding self-citations from the total citations, divide this result by the total number of citations, and then multiply by 100 to get the percentage. For instance, if the total citations are 12,526 and the citations excluding self-citations are 12,000, the difference of 526 self-citations divided by the total results in a rate of 4.199%. This percentage indicates how much self-citations add to the overall citation count, which is important for maintaining appropriate citation standards.